An Analysis of the Needs of the Counselor Profession in Rejang Lebong and Efforts to make it real - Syamsulrizal Syamsulrizal; Agus Riyan Oktori; Fadila Fadila; Eka Yanuarti (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to describe the professional needs of counselors in Rejang Lebong and to describe how the efforts of IAIN Curup in realizing the counselor profession are. This type of research is a qualitative research, using interview, observation and documentation analysis techniques. The results of this study indicate that first the Counselor Profession is urgently needed in Rejang Lebong because of environmental conditions that require a counselor profession and also the development of the industrial world resulting in the community needing a counselor profession. Due to the needs of great counselor of now day era, this study becomes a problem solver to find the great criteria which is needed for good counselor in the future. What is needed in Rejang Lebong is a counselor who has stable emotions, a counselor who can be used as an example, a counselor who has broad insight, a counselor who can be relied on, and has a solid personality of integrity. The two efforts of IAIN Curup in realizing the counselor profession are quite a lot, including in realizing S1 or S2 counseling guidance, and the existence of an educated profession, as well as the availability of facilities and infrastructure to support learning so that it will produce professional students both in terms of pedagogic, social, personality and personality competencies also profession. This research is limited on counselor characteristics and how to realize it, but this research needs deeper study to analysis counselor problem to become all around-counselor which means can handle every situation.